Exploring the potential of Cordyceps militaris cultivation on agricultural waste for sustainability and economic development - Balooni, Madhur; Sharma, Geeta; Bhatt, Bhagyashree (Mushroom Research, 2025)
Cordyceps militaris is utilized for several medicinal properties and is one of the high-priced mushrooms in the market. Cordycepin, the compound produce by the fungus, has a potent antibacterial action against the majority of bacterial species. The production of Cordyceps militaris is limited and to meet the market demand, the production needs to be increased. The insights into cultivationtechniques of the fungus are must to enhance its production. Thus, a study was conducted to evaluate the growth of fungus on seven different mediums and agriculture waste-based substrates. Amongst all the tested media, maximum radial growth was observed after 16 days in CZYA (6.8 cm) and OMA (6.7 cm). Use of Brown rice as a substrate resulted in maximum numbers of fruiting body production, in minimum number of days compared to other substrates.